Modeling the Effect of Power Consumption in Automated Driving Systems on Vehicle Energy Efficiency for Real-World Driving in California. Issue 4 (April 2019) - Hamza, Karim; Willard, John; Chu, Kang-Ching; Laberteaux, Kenneth P.
Vehicle automation has drawn much attention in recent years, as it is perceived to usher in new levels of safety, convenience, and energy efficiency in transportation. Much uncertainty and speculation still exist regarding how automated driving (AD) would affect the overall transportation energy, as a result of some factors that are difficult to predict, such as changes in driving patterns and induced travel demand. There is also much speculation about the optimum vehicle powertrain for which AD systems are to be mounted. This study focuses on a less discussed, less speculative issue that pertains to both transportation energy efficiency and powertrain suitability. The impact of the power consumption in an AD system (for sensors, data processing, and vehicle controls) is analyzed for various powertrains via a publicly open-source simulation code, for more than 59, 000 real-world vehicle trips obtained from the California Household Travel Survey. Study of scenarios of power consumption in the AD system that range from present-day values (about 3 kW) to future targets (0.5 kW) reveal interesting trends in vehicle energy efficiency. At 0.5 kW power consumption, the AD system can be of minimal impact to vehicle efficiency; however, at present-day levels of AD power consumption, the electric driving range (for electric vehicles and plug-in hybrids) could be shortened by 27–47% and fuel consumption could increase by up to 37% compared with the same vehicle model with no AD system.